2006
DOI: 10.1097/01.gim.0000214453.74456.f3
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis testing among Arab-Americans

Abstract: Purpose: Limited data regarding the cystic fibrosis carrier frequency and mutation detection rate is available for Arab-Americans. We retrospectively determined the frequency of carriers among Arab-Americans undergoing preconception and prenatal carrier screening in our laboratories. Methods: Between October, 2001 and June, 2005, we performed carrier screening on 805 Arab-Americans, testing for at least the original 25 mutations recommended by the American College of Medical Genetics. We compared our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Interestingly, the two common Arab mutations 1548delG and H139L, which were not found in any Caucasian chromosomes and were suggested to originate from the native Arab population, were absent from our study [15,28]. A possible explanation to differences between our results and those reported from other Arab studies may be due to the heterogeneous backgrounds of our families in contrast to the more pure Arab homogenous background from other studies [25].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the two common Arab mutations 1548delG and H139L, which were not found in any Caucasian chromosomes and were suggested to originate from the native Arab population, were absent from our study [15,28]. A possible explanation to differences between our results and those reported from other Arab studies may be due to the heterogeneous backgrounds of our families in contrast to the more pure Arab homogenous background from other studies [25].…”
Section: Discussioncontrasting
confidence: 83%
“…F508del was not as frequently reported in the Arab populations. Moreover, Arabs carry CFTR mutations that were never described in the Caucasians [15]. In this study, we describe the CFTR mutational spectrum in the Lebanese population.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, a panel of 11 common mutations accounting overall for 70% of all Arab CF chromosomes have been reported : ΔF508del, 3120 + 1G " A, N1303K, W1282X, G115X, 711 + 1G " A, S549R, I1234V, 1548delG , H139L and 4010del4 [9]. The latter three mutations are believed to have originated in the Arab native populations since they were never described in Caucasian CF patients [5][6][7][8].…”
Section: Discussionmentioning
confidence: 95%
“…Few studies have reported on Arab populations in general and only one study was conducted on the Lebanese population [4]. According to these reports, while ΔF508del mutation does not seem to account for more than 20% of all Caucasian CF chromosomes, several other mutations described in Arabs have never been described elsewhere [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 85%
“…Data suggest that more than 160 CFTR variants have been identified on approximately 3700 Asian CF chromosomes. Overall, F508del (p.Phe508del, c.1521_1523delCTT) remains the most common variant in Asian countries with few exceptions (Table ) . However, F508del constitutes only 12–31% of Asian CF alleles compared with 66% in the worldwide CF population comprised mainly from North America, Europe, Canada, Australia and New Zealand (http://www.genet.sickkids.on.ca/app).…”
Section: Distribution and Functional Consequences Of Cftr Variants Inmentioning
confidence: 99%